Manfaat pendirian koperasi untuk mengelola usaha penyewaan jasa alat dan mesin pertanian (UPJA): studi kasus di Kabupaten Karanganyar, Jawa Tengah - Hanggana, Sri (Analisis Kebijakan Pertanian, 2025)
The performance of the Business of Agricultural Tools and Machinery Rental Services (UPJA) managed by farmer groups in Kebakkramat District, Karang Anyar Regency, Central Java, was mostly ineffective. Only one out of 25 farmer groups effectively managed UPJA, namely Koperasi Jasa Simo Makmur. This research is a case study of this cooperative that aims to explore evidence of the benefits of cooperatives in increasing the effectiveness of UPJA. This study uses a qualitative method. The interview participants for this study were selected for cooperative management using the purposeful sampling method and for cooperative members using the snowball sampling method. Data were collected from February to April 2024 using in-depth interview techniques and focus group discussions. Data credibility was tested by extending the observation period, checking members, and triangulation. The main conclusion of this study is that establishing a cooperative can increase the effectiveness of UPJA management. The benefits for cooperative members are that they pay cheaper tractor rentals than market prices, and for cooperative management, they receive profit-sharing compensation. The cooperative has savings to buy new machines in the next eight to ten years. The heads of the farmer groups feel that they benefit from establishing the cooperative because the rights and obligations in managing UPJA are balanced.